Li2Se-C composite material, preparation method thereof and application of Li2Se-C composite material in lithium ion battery
The carbon-coated lithium selenide particles prepared by mixing lithium selenide with a carbon source under an inert atmosphere, the safety and cost problems of the existing lithium selenide preparation methods are solved, and efficient lithium replenishment performance and air stability are achieved. It is suitable for the positive electrode material of lithium-ion batteries.
Patent Information
- Application Number
- CN202411716535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
AI Technical Summary
The existing preparation methods of lithium selenide have problems such as low safety, high cost, complex operation and easy reaction in the air, resulting in increased production difficulty and cost.
Carbon-coated lithium selenide particles (Li2Se@C composite material) were prepared by mixing and heating the lithium selenide source under an inert atmosphere and applied to the positive lithium supplement agent of lithium ion batteries.
A simple, safe and low-cost lithium selenide preparation method is realized, which improves the air stability and lithium replenishment performance of the material. The actual lithium replenishment capacity exceeds 600mAh/g, and effectively suppresses volume expansion during battery use.
Smart Images

Figure CN119568998A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical materials and lithium ion batteries, and relates to a Li2Se@C composite material and a preparation method thereof and application in lithium ion batteries. Background Art
[0002] As a highly efficient energy storage device, lithium batteries are widely used in electric vehicles, portable electronic devices and other fields. Lithium selenide is considered to be an excellent positive electrode lithium replenisher for batteries due to its high theoretical specific capacity, suitable voltage range, and no gas production during the lithium replenishment process.
[0003] At present, the synthesis methods of lithium selenide mainly include: first, the reaction of selenium powder and lithium triethylborohydride in tetrahydrofuran. Although this method is feasible, it is costly and uneconomical; second, the reaction of selenium powder and lithium powder in liquid ammonia. Although this method has a low cost, the use of liquid ammonia greatly reduces the safety of the operation; third, the ball milling reaction of selenium powder and lithium hydride in an inert atmosphere avoids the use of toxic solvents, but safety hazards and high costs are still its main problems.
[0004] In addition, lithium selenide is very reactive in the air, which requires strict control of environmental conditions during its preparation and storage, further increasing the difficulty and cost of production. Therefore, developing a simple, economical method for preparing lithium selenide without the use of harmful solvents is of great significance for promoting its application in the industrial field. Summary of the invention
[0005] In order to solve the problems of low safety, high cost and complicated operation of the above-mentioned lithium selenide preparation method, the present invention provides a simple, safe and cost-effective Li2Se@C composite material and its preparation method and application in lithium-ion batteries. The method prepares carbon-coated lithium selenide particles by simple mixing, heating and other means, and applies them as positive electrode lithium supplement in lithium-ion batteries.
[0006] The technical solution provided by the present invention is as follows:
[0007] A method for preparing a Li2Se@C composite material, the method comprising the following steps:
[0008] Lithium selenite and a carbon source are ground and fully mixed in a molar ratio of 1:3-6, the mixture is placed in a reaction container, heated to 500°C to 1000°C under an inert atmosphere, and maintained at the temperature for 3-10 hours for sintering; after cooling, the mixture is taken out in an inert atmosphere to obtain a Li2Se@C composite material.
[0009] Furthermore, the carbon source includes one or more of Ketjen black, activated carbon, graphite, polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), sucrose, and glucose.
[0010] Furthermore, the hybrid method is any one of the following hybrid methods:
[0011] Ball milling;
[0012] Grind and mix in an agate mortar;
[0013] Dissolve one or two of them in the solution and perform rotary evaporation to obtain a uniformly mixed material.
[0014] Furthermore, before sintering, inert gas is passed to exhaust the air in the furnace.
[0015] Furthermore, the sintering temperature rise rate is 3-5°C per minute.
[0016] Furthermore, the inert gas is nitrogen, neon, argon or helium.
[0017] The Li2Se@C composite material preparation method comprises the following steps:
[0018] (1) Mix lithium selenite and a carbon source in a certain proportion.
[0019] (2) The mixed materials are placed in a container and placed in a furnace. Inert gas is introduced and a certain temperature is set for sintering.
[0020] (3) After cooling, the prepared lithium selenide particles are collected, and the obtained particles have a carbon-coated structure.
[0021] In the present invention, in the step (1), the particle size of lithium selenite is preferably nanometer-scale.
[0022] In the step (1), the carbon source is a carbon material such as Ketjen black, activated carbon, graphite, or an organic carbon source that can be carbonized in an inert gas such as carboxymethyl chitosan, phenolic resin, sucrose, glucose, PVDF, PEO, etc.
[0023] In the step (1), the chemical reaction equation involved is mainly: Li2SeO3+3C→ Li2Se+3CO↑.
[0024] In step (2), before sintering, the air in the furnace needs to be exhausted by passing inert gas. Before heating, the reaction vessel is evacuated by a vacuum pump and filled with inert gas to exhaust the air.
[0025] In step (3), the collected product needs to be stored in an air-tight manner.
[0026] The present invention also provides a Li2Se@C composite material, which is prepared by the above preparation method.
[0027] The present invention also provides application of the Li2Se@C composite material in lithium ion batteries.
[0028] Furthermore, the material is used in the positive electrode of a lithium-ion battery or a lithium-sulfur battery to improve the cycle stability and electrochemical performance of the battery.
[0029] Furthermore, the preparation method of the lithium-ion battery includes: mixing the Li2Se@C composite material with a conductive agent and a binder, and adding N-methylpyrrolidone to prepare a slurry, uniformly coating the slurry on an aluminum foil, drying and rolling to obtain a positive electrode sheet, and assembling the positive electrode sheet with a lithium sheet to obtain a lithium-ion battery.
[0030] Furthermore, the preparation method of the lithium-ion battery includes: mixing the Li2Se@C composite material and lithium iron phosphate, then mixing them again with a conductive agent and a binder, and adding N-methylpyrrolidone to prepare a slurry, uniformly coating the slurry on an aluminum foil, drying and rolling to obtain a positive electrode sheet, and assembling the positive electrode sheet with a lithium sheet and graphite to obtain a lithium-ion battery.
[0031] Beneficial Effects
[0032] The lithium selenide preparation method of the present invention is not only simple and low-cost, but also safe and environmentally friendly. The product obtained after calcination is carbon-coated lithium selenide particles. This composite material exhibits excellent lithium replenishment performance, and the actual lithium replenishment capacity exceeds 600mAh / g.
[0033] In addition, the introduction of the carbon coating layer not only improves the stability of lithium selenide in the air, but also allows it to exist stably in an air environment with a relative humidity of 25% for 1 hour without obvious changes.
[0034] The material of the present invention has the characteristic of "zero gas emission", avoids the generation of side reaction gas, and effectively inhibits the volume expansion of the battery during use compared with other lithium supplements. After adding this lithium supplement, the capacity retention rate of lithium iron phosphate in the graphite full battery is still 87.62% after 500 cycles, which is better than the battery without adding lithium supplement. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The figure is a flow chart for the preparation of carbon-coated lithium selenide particles;
[0036] Figure 2 X-ray diffraction (XRD) pattern of the composite material prepared from Ketjen black and lithium selenite;
[0037] Figure 3 X-ray diffraction (XRD) pattern of composite materials prepared from polyvinylidene fluoride (PVDF) and lithium selenite;
[0038] Figure 4 X-ray diffraction (XRD) pattern of composite materials prepared from polyacrylonitrile (PAN) and lithium selenite;
[0039] Figure 5 It is a standard X-ray diffraction (XRD) card of lithium selenide;
[0040] Figure 6 X-ray diffraction (XRD) patterns of Li2Se@C composite materials before and after exposure to air for 1 h;
[0041] Figure 7 X-ray diffraction (XRD) patterns of commercial Li2Se before and after exposure to air for 1 hour;
[0042] Figure 8 Scanning electron microscope (SEM) image of the composite material prepared by carbothermal reduction of Ketjen black and lithium selenite;
[0043] Fig. 9 is the electrochemical performance diagram of the composite material;
[0044] Fig.10 This is the electrochemical performance diagram of the composite material in lithium iron phosphate half-cell;
[0045] Fig.11 This is the electrochemical performance diagram of lithium iron phosphate half-cell;
[0046] Fig.12 is the X-ray photoelectron spectroscopy (XPS) graph of the composite material;
[0047] Fig.13 This is the electrochemical performance diagram of the composite material in a lithium iron phosphate-graphite full battery;
[0048] Fig.14 This is the electrochemical performance diagram of lithium iron phosphate-graphite full battery. DETAILED DESCRIPTION
[0049] The present invention is described in more detail below through specific examples. The examples provided are only used to illustrate the present invention, but do not limit the protection scope of the present invention in any way.
[0050] Example 1
[0051] This embodiment provides a Li2Se@C composite material, and the preparation method thereof includes:
[0052] Take 1 g of lithium selenite and 0.2 g of Ketjen black, use a planetary ball mill for dry grinding, set the speed to 400 r / min, and ball mill for 24 h to ensure that the two are fully in contact and evenly distributed.
[0053] The mixed materials were transferred into a quartz tube and argon gas was introduced for 20 minutes to remove the residual oxygen in the furnace.
[0054] The furnace temperature was raised to 750° C. at a rate of 5° C. / min and maintained at this temperature for 10 hours for calcination to complete the synthesis of lithium selenide.
[0055] After completion, the composite material was naturally cooled to room temperature and taken out.
[0056] The obtained composite materials were characterized by X-ray diffraction (XRD). Figure 2 ). Compare to standard cards (see Figure 5 ), confirming that the prepared material is lithium selenide. Take 1g of the prepared composite material and 1g of commercial Li2Se material and expose them to air with a relative humidity of 25% for 1 hour for X-ray diffraction (XRD) characterization (see Figure 6 and Figure 7 ). The results show that the composite material has almost no change, while the commercial Li2Se has undergone significant deterioration, indicating that the prepared composite material has better air stability, which is due to the effective air barrier of the surface carbon coating.
[0057] Example 2
[0058] Take 1 g of lithium selenite and 0.4 g of polyvinylidene fluoride (PVDF), grind and mix them using an agate mortar to ensure that the two are fully in contact and evenly distributed.
[0059] The mixed materials were transferred into a quartz tube, and the tube furnace was preheated to room temperature. Argon gas was introduced for 20 minutes to remove the residual oxygen in the furnace.
[0060] The furnace temperature was raised to 600°C at a rate of 3°C / min and maintained at this temperature for 8 hours to complete the synthesis of lithium selenide.
[0061] After completion, the composite material was naturally cooled to room temperature and taken out.
[0062] The obtained composite materials were characterized by X-ray diffraction (XRD). Figure 3 ). Compare to standard cards (see Figure 5 ), confirming that the prepared material is lithium selenide.
[0063] Example 3
[0064] Take 1 g of lithium selenite and 0.4 g of polyacrylonitrile (PAN), grind and mix them using an agate mortar to ensure that the two are fully in contact and evenly distributed.
[0065] The mixed materials were transferred into a quartz tube, and the tube furnace was preheated to room temperature. Argon gas was introduced for 20 minutes to remove the residual oxygen in the furnace.
[0066] The furnace temperature was raised to 800°C at a rate of 5°C / min and maintained at this temperature for 9 hours to complete the synthesis of lithium selenide.
[0067] After completion, the composite material was naturally cooled to room temperature and taken out.
[0068] The obtained composite materials were characterized by X-ray diffraction (XRD). Figure 4 ). Compare to standard cards (see Figure 5 ), confirming that the prepared material is lithium selenide.
[0069] Example 4
[0070] In the process of preparing the positive electrode material of the battery, the Li2Se@C composite material prepared by the method of Example 1 is first mixed with the conductive agent Ketjen black and the binder PVDF in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) is added to prepare a slurry. The slurry is evenly coated on an aluminum foil, then dried at 80°C and formed into a positive electrode sheet by a rolling process. Then, the positive electrode sheet is assembled into a battery together with a metal lithium sheet to obtain a Li2Se half-cell.
[0071] The battery was electrochemically tested (see Fig. 9 ): First, charge to 4.2V at 0.1C for lithium replenishment, then cycle at 0.1C between 2.5V-3.8V to simulate the normal working state of the battery. The results show that the first charge capacity is as high as 620mAh / g, there is basically no capacity during the discharge process, and there is no obvious charge and discharge behavior in subsequent cycles. This shows that the composite material has excellent lithium replenishment performance and has the potential for application as a lithium replenisher.
[0072] The Li2Se@C composite material (accounting for 4wt%) and lithium iron phosphate (accounting for 92wt%) prepared in Example 3 are mixed in proportion. The mixture is mixed again with the conductive agent Ketjen black and the binder PVDF in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone is added to prepare a slurry. This slurry is also coated on aluminum foil, and the positive electrode sheet is obtained after drying and rolling. Next, the positive electrode sheet is assembled into a battery with a metal lithium sheet to obtain a lithium iron phosphate half-cell, and then the positive electrode sheet is assembled into a battery with a graphite electrode sheet to obtain a lithium iron phosphate full battery.
[0073] The battery assembled in Example 4 was subjected to electrochemical testing according to the procedure of 0.1C charge and discharge activation for the first two cycles and 1C cycle for the subsequent cycles. The electrochemical performance of the half-cell was obtained as follows: Fig.10 and Fig.11 shown. Fig.10 The cycling performance of the lithium iron phosphate half-cell with the addition of Li2Se@C composite material is shown. Fig.11), the capacity of the half-cell remained stable at about 125 mAh / g, which is about 5 mAh / g higher than the capacity without the composite material. This performance improvement is due to the excellent conductivity of the Li2Se@C composite material, which effectively enhances the conductivity of the positive electrode, thereby improving the overall performance of the battery. There is no obvious difference in the cycle performance of the two, indicating that the addition of the composite material has no negative effect on the lithium iron phosphate positive electrode.
[0074] The excellent conductivity of the composite material is due to two aspects: on the one hand, the overall conductivity is improved due to the introduction of carbon materials; on the other hand, the XPS analysis results show the presence of Se-C bonds in the material (see Fig.12 ), indicating that a close chemical contact is formed between the lithium selenide particles and the surface carbon material. This bonding not only enhances the structural stability of the composite material, but also effectively improves the conductive properties of the lithium selenide itself.
[0075] Fig.13 The performance of the lithium iron phosphate full battery after adding the Li2Se@C composite material was demonstrated. After 500 cycles, the battery capacity retention rate of the composite material was 87.62%, and the capacity was maintained at 110 mAh / g; in contrast, the capacity retention rate of the lithium iron phosphate battery without the composite material under the same conditions was only 57.38% (see Fig.14 ), showing a faster capacity decay. The results show that the addition of Li2Se@C composite material significantly improves the stability of the battery. This improvement is due to the fact that the composite material embeds excess lithium ions into the negative electrode graphite during charging to offset the consumption of lithium ions in subsequent cycles, thereby effectively slowing down the capacity decay.
[0076] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a Li2Se@C composite material, characterized in that: The method comprises the following steps: Lithium selenite and a carbon source are ground and fully mixed according to a molar ratio of 1:3-6, the mixture is placed in a reaction container, heated to 500-1000°C under an inert atmosphere, and the temperature is maintained for 3-10 hours for sintering; after cooling, the mixture is taken out in an inert atmosphere to obtain a Li2Se@C composite material.
2. The method for preparing the Li2Se@C composite material according to claim 1, characterized in that: The carbon source includes one or more of Ketjen black, activated carbon, graphite, PVDF, PEO, PAN, sucrose, and glucose.
3. The method for preparing the Li2Se@C composite material according to claim 1, characterized in that: The hybrid method is any of the following hybrid methods: Ball milling; Grind and mix in an agate mortar; Dissolve one or two of them in the solution and perform rotary evaporation to obtain a uniformly mixed material.
4. The method for preparing the Li2Se@C composite material according to claim 1, characterized in that: Before sintering, the air in the furnace is exhausted by passing inert gas.
5. The method for preparing the Li2Se@C composite material according to claim 1, characterized in that: The sintering temperature rise rate is 3~5℃ per minute.
6. The method for preparing the Li2Se@C composite material according to claim 1, characterized in that: The inert gas is nitrogen, neon, argon or helium.
7. A Li2Se@C composite material, characterized in that: The method is prepared by any one of claims 1 to 6.
8. Use of the Li2Se@C composite material according to claim 7 in lithium-ion batteries.
9. The use according to claim 8, characterized in that: The preparation method of the lithium ion battery comprises: mixing the Li2Se@C composite material with a conductive agent and a binder, and adding N-methylpyrrolidone to prepare slurry, uniformly coating the slurry on an aluminum foil, drying and rolling to obtain a positive electrode sheet, and assembling the positive electrode sheet with a lithium sheet to obtain a lithium ion battery.
10. The use according to claim 8, characterized in that: The preparation method of the lithium ion battery comprises: mixing the Li2Se@C composite material and lithium iron phosphate, then mixing them again with a conductive agent and a binder, adding N-methylpyrrolidone to prepare a slurry, uniformly coating the slurry on an aluminum foil, drying and rolling to obtain a positive electrode sheet, and assembling the positive electrode sheet with a lithium sheet and graphite to obtain a lithium ion battery.